Analysis of Education-Based Curriculum Policy at SD 070851 Medan - Yesica Siallagan; Sari Mutiah Siregar; Tryona Loise Siahaan; Natalia Rama Kudadiri; Agum Budianto (LP3M KH Yazid Karimullah Institute, 2025)
This research endeavors to examine the curriculum policy at SD 070851 Medan, with a particular focus on its influence on educational quality and the character development of students. Employing a qualitative methodology, the study gathered data through interviews, observations, and analysis of relevant documents. The results reveal that the curriculum not only aligns with academic standards but also incorporates local cultural values that are crucial for shaping students' identities. Nonetheless, the study identifies challenges such as insufficient resources and the preparedness of educators to implement the new curriculum effectively. The research underscores the importance of collaboration among various stakeholders to foster an improved learning environment and enhance the success of primary education.